Iron‐Catalyzed Synthesis of the Hexahydrocyclopenta[c]furan Core and Concise Total Synthesis of Polyflavanostilbene B. Issue 32 (16th July 2018) - Wang, Xujie; Liu, Fu; Yun, Juping; Feng, Ziming; Jiang, Jianshuang; Yang, Yanan; Zhang, Peicheng
Abstract: The first synthesis of polyflavanostilbene B (1 ), which has seven contiguous stereocenters including two quaternary carbon centers, from abundant polymeric (−)‐epicatechin gallate on a gram scale in three steps without the use of protecting groups is reported. The key transformations of this strategy include a regioselective and stereoselective substitution of resveratrol to give the 4‐derivative of (−)‐epicatechin 3‐gallate and an iron‐catalyzed cyclization reaction. The possible radical cyclization mechanism in the formation of the hexahydrocyclopenta[c]furan core is also discussed. Abstract : Straightforward : Polyflavanostilbene B (1 ) was synthesized for the first time from abundant polymeric (−)‐epicatechin gallate on a gram scale in three steps without the use of protecting groups. The key transformations of this strategy include the regioselective and stereoselective substitution of resveratrol to give the 4‐derivative of (−)‐epicatechin 3‐gallate and an iron‐catalyzed cyclization.